Madeira : the islands and their wines. - Mayson, Richard (The Infinite Ideas classic wine library, 2015)
Madeira wines from the nineteenth and even the eighteenth centuries still retain an ethereal, youthful gloss. Once the cork is removed, the wine comes to no harm, even if the bottle is left open and on ullage for months on end. If ever there was a wine to take to a desert island, this is it. Although Madeira was only discovered in the fifteenth century, the island and the wine trade have a long and involved history. After a short historical introduction Madeira: The Island and its Wines rounds on the present: the physical character of the archipelago, the state of the vines and vineyards and t.